2023
DOI: 10.3390/app13042232
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Tartary Buckwheat to Plastic Mulching and Fertilization on Semiarid Land

Abstract: Integrated hole-sowing, fertilization, and plastic mulching techniques are common agronomic practices applied to collect rainwater and to improve rainwater utilization in semiarid rain-fed regions. However, little is known about the growth responses of tartary buckwheat (Fagopyrum tataricum L.) to the practices adopted in semiarid areas of Loess Plateau in Northwest China. To address the concerns, a long-term field experiment was conducted in 2015–2017. Four fertilization levels, namely, high fertilization lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our results confirmed that, in the semi-arid areas of the Loess Plateau, water consumption and WUE were also jointly affected by natural factors (e.g., precipitation, temperature, etc.) and cultivation practices (e.g., plastic film mulching) [19]. Plastic film mulching can reduce soil water dissipation and increase soil water storage compared to non-mulching.…”
Section: Effects Of Plastic Film Mulching and Fertilizer Application ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our results confirmed that, in the semi-arid areas of the Loess Plateau, water consumption and WUE were also jointly affected by natural factors (e.g., precipitation, temperature, etc.) and cultivation practices (e.g., plastic film mulching) [19]. Plastic film mulching can reduce soil water dissipation and increase soil water storage compared to non-mulching.…”
Section: Effects Of Plastic Film Mulching and Fertilizer Application ...mentioning
confidence: 99%
“…Soil nutrients are another pivotal factor affecting crop growth and yield formation, and reasonable fertilizer application can significantly improve crop productivity [18]. Consequently, optimizing fertilizer utilization and facilitating efficient use of natural precipitation is pivotal for increasing yield and enhancing water and fertilizer use efficiency in the semi-arid Loess Plateau [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation